Oxide film defects in Al alloys and the formation of hydrogen- related porosity. Issue 1 (March 2016) - Griffiths, W D; Gerrard, A J; Yue, Y
Abstract: Double oxide film defects have also been held responsible for the origins of hydrogen porosity, where hydrogen dissolved in the Al melt passes into the interior atmosphere of the double oxide film defect causing it to inflate. However, this is in opposition to long- established evidence that H cannot readily diffuse through aluminium oxide. To investigate this further, samples of commercial purity Al were first degassed to remove their initial H content, and then heated to above their melting point and held in atmospheres of air and nitrogen respectively, to determine any differences in H pick-up. The experiment showed that samples held in an oxidising atmosphere, and having an oxide skin, picked up significantly less H than when the samples were held in a nitrogen atmosphere, which resulted in the formation of AlN in cracks in the oxide skin of the sample. It is suggested that double oxide film defects can give rise to hydrogen-related porosity, but this occurs more quickly when the oxygen in the original oxide film defect has been consumed by reaction with the surrounding melt and nitrogen reacts to form AlN, which is more permeable to H than alumina, more easily allowing the oxide film defect to give rise to a hydrogen pore. This is used to interpret results from an earlier synchrotron experiment, in which a small pore was seen to grow into a larger pore, while an adjacent large pore remained at a constant size.